Maternal wellbeing five years after a very preterm delivery: prevalence and influencing factors in a European cohort - Wohlers, L; Maier, RF; Cuttini, M; Wilson, E; Benhammou, V; Lebeer, J; Laroche, S; Sarrechia, I; Petrou, S; Thiele, N; Zeitlin, J; Aubert, AM (MDPI, 2023)
(1) Background: Mothers of very preterm (VPT) infants may experience psychological symptoms compromising long-term emotional wellbeing. This study describes the emotional wellbeing of mothers of five-year-old children born VPT. We assess the association between sociodemographic, perinatal and neonatal characteristics, and the child’s health and development at five years old and maternal emotional wellbeing. (2) Methods: Data are from the prospective European “Effective Perinatal Intensive Care in Europe” (EPICE) and subsequent “Screening for Health In very Preterm infantS in Europe” (SHIPS) projects including births <32 weeks’ gestational age in 11 countries in 2011/12. Data were abstracted from obstetric and neonatal records. At five years old, 2605 mothers answered a parental questionnaire including the Mental Health Inventory-5 (MHI-5). Associations between sociodemographic and health characteristics and the mother’s MHI-5 score were investigated using multilevel multivariate linear regression analysis with the country modelled as a random effect and inverse probability weighting to correct for attrition bias. (3) Results: The mean MHI-5 score was 71.3 (SD 16.7) out of 100 (highest emotional wellbeing) with a variation among countries from 63.5 (SD 16.8; Poland) to 82.3 (SD 15.8; the Netherlands). MHI-5 scores were significantly lower for mothers whose child had a severe health problem, developmental, or speech delay, for multiparous and single mothers, and when at least one of the parents was unemployed. (4) Conclusions: The emotional wellbeing of mothers of VPT infants differs between European countries. Identifying sociodemographic characteristics and child’s health and developmental conditions that affect maternal emotional wellbeing may help to identify groups of mothers who need special assistance to cope with consequences of the delivery of a VPT child.